Current status of research on the application of robot-assisted transanal rectal surgery - Zheng Peng; Zhang Chaojun (结直肠肛门外科)
Robot-assisted transanal rectal surgery, as an emerging technology, has achieved certain successes in clinical applications, as reported in the literature. However, consensus has not yet been reached on the recommendations for choosing surgical approaches and standards for evaluating its effectiveness. Starting from the two surgical methods of robot-assisted transanal total mesorectal excision and robot-assisted transanal minimally invasive surgery, this article combines literature data with the clinical practice experience of the authors’ team to elaborate on the current status of research on the application of robot-assisted transanal rectal surgery. It discusses the limitations and issues in this type of surgery at the present stage and briefly explores the future development directions of such surgeries.